A comparison of disease caused by Shigella and Campylobacter species: 24 months community based surveillance in 4 slums of Karachi, Pakistan - Sajid Bashir Soofi; Muhammad Atif Habib; Lorenz von Seidlein; Muhammad Jawed Khan; Shah Muhammad; Naveed Bhutto; Mohammad Imran Khan; Shahid Rasool; Afia Zafar; John D. Clemens; Qamaruddin Nizami; Zulfiqar A. Bhutta (Elsevier, 2011)
Summary: Despite the efforts of the international community diarrheal diseases still pose a major threat to children in children less than five years of age. Bacterial diarrhea has also emerged as a public health concern due to the proliferation of drug resistant species in many parts of the world. There is a paucity of population-based data about the incidence of shigellosis and Campylobacter infections in Pakistan. We report country specific results for Shigella diarrhea that were derived from a multicenter study conducted in six Asian countries. Disease surveillance was conducted over a 24 month period in urban slums of Karachi, Pakistan, a city with a population of 59,584. Cases were detected through passive detection in study treatment centers. Stool specimens or rectal swabs were collected from all consenting patients. Between January 2002 and December 2003 10,540 enteric infection cases were detected. The incidence rate of treated diarrhea in children under 5 was 488/1000/year. In children, 5 years and older, the diarrhea rate was 22/1000/year. 576 (7%) Campylobacter isolates were detected. The pre-dominant Campylobacter species was C. jenuni with an increase of 29/1000 year in children under 5 years. Shigella species were isolated from 394 of 8032 children under 5 years of age. Shigella flexneri was the dominant species (10/1000/year in children under 5 years) followed by Shigella sonnei (3.9/1000/year), Shigella boydii (2.0/1000/year) and Shigella dysenteriae (1.3/1000/year). Shigellosis and Campylobacter infection rates peaked during the second year of life. The incidence rate of shigellosis increased in old age but such a trend was not observed in Campylobacter infections. Of 394 shigellosis patients 123 (31%) presented with dysentery in contrast to only 54 (9%) of 576 patients with Campylobacter infections (p < 0.001). Both Campylobacter infections and shigellosis are common in community settings of Pakistan but shigellosis presented more frequently with abdominal pain and dysentery than Campylobacter infections indicating that shigellosis may be a more severe illness than Campylobacter infections. Due to the increased and disease severity, drug resistant shigella have become a significant health problem; moreover it is a disease of poor and impoverished people who do not have the access to standard water and sanitary conditions, health care services or optimal treatment. In the face of these facts it is empirically important to develop a low cost effective vaccine that can protect these populations for a longer duration. Keywords: Diarrhea, Campylobacteriosis, Shigellosis, Children, Epidemiology